EFFECT OF TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND ORGANIZATIONAL COMMITMENT (Study of Employee Dr. Soetomo University Surabaya) - Suyanto Suyanto (Yos Soedarso Economic Journal (YEJ), 2019)
The importance of organizational commitment will have an impact on organizational performance, and for the organization need to foster organizational citizenship behavior, which is influenced by the presence of the behavior of transformational leadership and job satisfaction of employees. For this study aims to determine the effect of transformational leadership and organizational citizenship behavior satisfaction and organizational commitment.Gathering of date through questionnaires given to 105 employees at the University Dr. Soetomo by purposive sampling. The results show the value of F = 8,275 and p = 0,000 (p<0,01) proves that there is simultaneous effect of transformational leadership and job satisfaction on organizational citizenship behavior . The results obtained by the partial analysis of the value of t test = 1,067 and p = 0,288 (p> 0,05) which means that transformational leadership has no effect on organizational citizenship behavior. Partial analysis also prove the existence of a significant effect of job satisfaction on organizational citizenship behavior with a value of t test= 3,106 and p = 0,002 (p<0,05). The results of the regression analysis testing also proved the influence of organizational citizenship behavior on organizational commitment obtained value F = 38,167 and p = 0,000 (p<0,01). Coefficient of determination known simultaneous transformational leadership and job satisfaction able to contribute effectively to organizational citizenship behavior by 14%, while organizational citizenship behavior able to contribute effectively to organizational commitment by 27% .Â Keywords:Â  transformational leadership, job satisfaction, organizational citizenship behavior, organizational commitment